Spatial analysis of infrastructure services in the Kadhimiya municipality unit: Electric and drinking water - Nour, Fatima; Jabor, Entezar (Al-Adab Journal, 2024)
The research aims to study the geographical distribution of the infrastructure company in the Al-Kadhimiya municipal unit (potable water service available for electricity specifically) because of its importance and importance in daily life for choice Service institutions have their own geographical differences, including what is compatible with population growth and what these services need and their connections, including their availability to enable the capabilities of that community, that is, its available natural and human resources that can provide it with a future that contributes to achieving development. The study area includes six neighborhoods: (Al-Kadhimiya neighborhood, Al-Zahraa neighborhood, Al-Fajr neighborhood, Ji Al-Salam, Al-Atifiyah neighborhood, and Al-Taji neighborhood), and there are drinking water services and electrical energy services. In the study area. These projects are distributed in proportion to the presence of residents within the old neighborhoods of the study area, while these services are significantly reduced in the Taji neighborhood, given that it is a newly established and developed neighborhood. As for the research problem: What are the drinking water and electric energy services projects in the Kadhimiya municipality unit and what is their geographical distribution? The number of drinking water stations in the study area was (2): the Kadhimiya Water Project and the Karama Water Project. The number of electrical power generation stations in the study area is (3 main and 7 secondary), and among these stations are the Justice Station and the Baghdad Belt. One of the neighborhoods in greatest need of infrastructure services in the study area is the Taji neighborhood.